Post a New Question


posted by .

Solve the IVP

{y'=-(sinx)y + xexp(cosx)
y(0) = 1

Please show me step by step. Do I need to find out if this is exact? Do I use an integrating factor?

  • Calculus -

    Solve the homogeneous equation first:

    y_h' = - sin(x) y_h ---->

    y_h(x) = K exp[cos(x)]

    Then, to find the solution, you use the variation of the constant method, i.e. take the solution of the homogeneous solution y_h and there you replace K by an unknown function K(x):

    y(x) = K(x) exp[cos(x)]

    If you substitute this in the differential equation then what happens is that only the term proportional to K' survives. Due to the product rule the terms proportional to K are what you would get if K were a constant, but these terms will satisfy the homogeneous equation, so they will sum to zero.

    So, what you get is:

    K' Exp[cos(x)] = x Exp[cos(x)] ----->

    K = 1/2 x^2 + c ----->

    y(x) = (1/2 x^2 + c)Exp[cos(x)]

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question